Toward a framework for understanding translation and interpreting teacher role identity - Chen, Bacui; Huang, Jing (Frontiers in Psychology, 2022)
The purpose of this paper is to present a translation and interpreting (T&I) teacher role identity (TITRI) framework for investigating how T&I teachers in China develop their role identities. There is a vast literature on language teacher identity in higher education compared to a paucity of literature on the development of T&I teacher identity. Developing a strong T&I teacher identity in the context of Chinese universities is challenging as teachers combine sub-roles of trainers/educators, researchers, and practitioners, and the context is generally more supportive of constructing a researcher role than trainer/educator and practitioner roles. A strong teacher identity, on the other hand, is vital since it enhances teachers’ willingness to engage in professional development. This study proposes a framework based on the Dynamic Systems Model of Role Identity (DSMRI) that describes how three sub-roles interact and contribute to an overall T&I teacher identity. This work contributes to the scant literature on T&I teacher identity research, shedding light on how different role identities may interact throughout the professional careers of a teacher. Additionally, the framework may also foster an awareness of the impact of higher education on a teacher and, as a result, offer implications for universities in China to encourage the development of teacher identity.